Efficiency and cost optimization of a regenerative Organic Rankine Cycle power plant through the multi-objective approach. (5th March 2017) - Gimelli, A.; Luongo, A.; Muccillo, M.
Highlights: Multi-objective optimization method for ORC design has been addressed. Trade-off between electric efficiency and overall heat exchangers area is evaluated. The heat exchangers area was used as objective function to minimize the plant cost. MDM was considered as organic working fluid for the thermodynamic cycle. Electric efficiency: 14.1–18.9%. Overall heat exchangers area: 446–1079 m 2 . Abstract: Multi-objective optimization could be, in the industrial sector, a fundamental strategic approach for defining the target design specifications and operating parameters of new competitive products for the market, especially in renewable energy and energy savings fields. Vector optimization mostly enabled the determination of a set of optimal solutions characterized by different costs, sizes, efficiencies and other key features. The designer can subsequently select the solution with the best compromise between the objective functions for the specific application and constraints. In this paper, a multi-objective optimization problem addressing an Organic Rankine Cycle system is solved with consideration for the electric efficiency and overall heat exchangers area as quantities that should be optimized. In fact, considering that the overall capital cost of the ORC system is dominated by the cost of the heat exchangers rather than that of the pump and turbine, this area is related to the cost of the plant and so it was used to indirectly optimize the economic system performance. For this reason, although cost data have not been used, the heat exchangers area was used as a second objective function to minimize the plant cost. Pareto optimal solutions highlighted a trade-off between the two conflicting objective functions. Octamethyltrisiloxane (MDM) was considered organic working fluid, while the following input parameters were used as decision variables: minimum and maximum pressure of the thermodynamic cycle; superheating and subcooling temperature; and regenerator heat exchanger efficiency. Four different solutions belonging to the Pareto optimal front were selected and analyzed. These solutions are characterized by a range of the electric efficiency between 14.1% and 18.9% and overall heat exchangers area from 446 m 2 to 1079 m 2 .